2020
DOI: 10.3389/fimmu.2020.565165
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil: A New Player in Metastatic Cancers

Abstract: The interaction between cancer cells and immune cells is important for the cancer development. However, much attention has been given to T cells and macrophages. Being the most abundant leukocytes in the blood, the functions of neutrophils in cancer have been underdetermined. They have long been considered an "audience" in the development of cancer. However, emerging evidence indicate that neutrophils are a heterogeneous population with plasticity, and subpopulation of neutrophils (such as low density neutroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 151 publications
(178 reference statements)
0
60
0
1
Order By: Relevance
“…As stated before in this manuscript, the NLR ratio is becoming a reliable biomarker for prognostic and predictive stratification in NSCLC ( Boscolo et al, 2020 ). Moreover, PMNs are recruited to distant organs through CXCR2/4 signaling and foster pre-metastatic niche formation ( Wu, 2020 ).…”
Section: Neutrophil Recruitment and Function In Lung Cancermentioning
confidence: 99%
“…As stated before in this manuscript, the NLR ratio is becoming a reliable biomarker for prognostic and predictive stratification in NSCLC ( Boscolo et al, 2020 ). Moreover, PMNs are recruited to distant organs through CXCR2/4 signaling and foster pre-metastatic niche formation ( Wu, 2020 ).…”
Section: Neutrophil Recruitment and Function In Lung Cancermentioning
confidence: 99%
“…As noted, although DTCs can migrate as single cells, collective migration is a more efficient route for metastasis [ 61 ]. Tumor-associated neutrophils and macrophages (TAMs), as well as myeloid-derived suppressor cells (MDSCs), promote collective migration and intravasation of tumor cells [ 33 , 62 , 63 ]. Under the influence of colony-stimulating factor 1 (CSF1), TAMs also promote angiogenesis.…”
Section: The Tumor Microenvironmentmentioning
confidence: 99%
“…The role of neutrophils in the pre-metastatic niche has not been fully explored. Neutrophils are innate immune cells that maintain tissue homeostasis by adjusting their function in response to various stimuli [121,122] . Although initially thought to not play an active role in cancer development, through the use of preclinical models, it has been demonstrated that different subpopulations of neutrophils modulate cancer metastasis [123] .…”
Section: Resident Cell Contributions To the Establishment Of The Brain Premetastatic Nichementioning
confidence: 99%